2022
DOI: 10.3389/fchem.2022.1013788
|View full text |Cite
|
Sign up to set email alerts
|

The antimicrobial peptide Magainin-2 interacts with BamA impairing folding of E. coli membrane proteins

Abstract: Antimicrobial peptides (AMPs) are a unique and diverse group of molecules endowed with a broad spectrum of antibiotics properties that are being considered as new alternative therapeutic agents. Most of these peptides are membrane-active molecules, killing bacteria by membrane disruption. However, recently an increasing number of AMPs was shown to enter bacterial cells and target intracellular processes fundamental for bacterial life. In this paper we investigated the mechanism of action of Maganin-2 (Mag-2), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The antimicrobial peptide magainin‐2 (Mag‐2) from Xenopus laevis binds BamA with high affinity, and impairs its function as the insertase for nOMPs (di Somma et al, 2022). Mag‐2 also disrupts the membrane by pore formation, triggering cell death (Billah et al, 2022; Maher & McClean, 2006).…”
Section: Bam Complex Inhibitors As Novel Therapeuticsmentioning
confidence: 99%
See 3 more Smart Citations
“…The antimicrobial peptide magainin‐2 (Mag‐2) from Xenopus laevis binds BamA with high affinity, and impairs its function as the insertase for nOMPs (di Somma et al, 2022). Mag‐2 also disrupts the membrane by pore formation, triggering cell death (Billah et al, 2022; Maher & McClean, 2006).…”
Section: Bam Complex Inhibitors As Novel Therapeuticsmentioning
confidence: 99%
“…Molecular docking analyses showed that Mag‐2 binds the lumen of BamA, thereby, either blocking OMPs from folding inside the BamA β‐barrel, or hindering the conformational changes of BamA required during OMP folding. OMP levels decrease after Mag‐2–BamA binding (di Somma et al, 2022). Mag‐2 however, displays cytotoxicity (Wade et al, 2022).…”
Section: Bam Complex Inhibitors As Novel Therapeuticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Antimicrobial properties of NAMPs, including gramicidin S from B. brevis [ 210 ], polymyxin B and A from B. polymyxa or vancomycin produced by S. orientalis [ 211 ], have been reported in several studies [ 207 , 212 ]. Similarly, magainin-2 extracted from amphibians, such as frog skin, showed antibacterial activity against MDR strains, protozoa, yeasts, and fungi [ 213 ]. Crotalicidin extracted from rattlesnakes killed 90% of E. coli and P. aeruginosa cells within 90–120 min and 5–30 min, respectively [ 214 ].…”
Section: Qs Pathways Inhibitionmentioning
confidence: 99%